The Efficacy of Performance Appraisal to Increase Employeesâ Job Satisfaction - Mahardayani, Iranita Hervi; Dhania, Dhini Rama (Journal of Educational, Health and Community Psychology, 2016)
AbstractThis research aimsÂ  to find out the effectiveness of implementation performance appraisal toward job satisfaction of employees UMKM Bordir Dahlia in Kabupaten Kudus. Sampling was done by using population studies to 16 employees of UMKM embroidery Dahlia Kudus. The type of this research is quantitative with pra experiment approached by One group pre and posttest design method. Data analysis on this research using non parametric with different test techniques Wilcoxon t-tes. The analysis result of different test scale job satisfaction before and after handling obtained Â Z = - 1,268, with p = 0,205 (p>0,05), so that there is no differences on job satisfaction on employees of embroidery Dahlia before and after treatment by giving performance appraisal. It means treatment by giving performance appraisal unable to increase employees job satisfaction. Therefore, the hypothesis on this research is rejected.Keywords : performance appraisal, Job satisfaction